Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s10519-006-9066-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Vulnerabilities Underlying Adolescent Substance Use and Problem Use: General or Specific?

Abstract: Are genetic and environmental risks for adolescent substance use specific to individual substances or general across substance classes? We examined this question in 645 monozygotic twin pairs, 702 dizygotic twin pairs, 429 biological sibling pairs, and 96 adoptive (biologically unrelated) sibling pairs ascertained from community-based samples, and ranging in age from 12 to 18 years. Substance use patterns and symptoms were assessed using structured psychiatric interviews. Biometrical model fitting was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
134
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 170 publications
(142 citation statements)
references
References 47 publications
(49 reference statements)
6
134
0
2
Order By: Relevance
“…This might be explained by the fact that we assessed associations between one twin's frequency of use in 1993 with the other twin's problem drinking in 1995 and 2000, while in classical twin studies drinking of twins is assessed with identical measures at the same point in time. The relative importance of genetic and environmental effects on problem drinking in young people has been rarely studied, only Young et al [40] showed that the variance in problem drinking in adolescents was for 53% explained by genetics and for 46% by environmental factors. All of these findings suggest that genes might play a role in problem drinking.…”
Section: Discussionmentioning
confidence: 99%
“…This might be explained by the fact that we assessed associations between one twin's frequency of use in 1993 with the other twin's problem drinking in 1995 and 2000, while in classical twin studies drinking of twins is assessed with identical measures at the same point in time. The relative importance of genetic and environmental effects on problem drinking in young people has been rarely studied, only Young et al [40] showed that the variance in problem drinking in adolescents was for 53% explained by genetics and for 46% by environmental factors. All of these findings suggest that genes might play a role in problem drinking.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of Colorado adolescents, Young et al, (2006) found high heritability for tobacco use (0.46), marijuana use (0.44), problem alcohol use (0.70) and problem marijuana use (0.64). Other studies have also shown that genetic and environmental factors may contribute to a general predisposition to illicit drug use rather than a substance-specific effect (Kendler et al, 2003;Karkowski et al, 2000;Agrawal et al, 2004;Uhl, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that genetic factors contribute to tobacco and alcohol problem use has been well established through adoption, twin, and family studies (2)(3)(4)(5)(6)(7)(8)(9)(10). Additionally, behavioral genetics studies strongly suggest that problem use of alcohol and tobacco may be due in part to genetic factors common to the etiology of use of both substances (11)(12)(13)(14)(15)(16)(17)(18). However, our understanding of the specific genetic factors and underlying molecular mechanisms remains limited.…”
Section: Introductionmentioning
confidence: 99%